Healing mushrooms eaudiobook A practical and culinary guide to using mushrooms for whole body health. - Isokauppila, Tero (Tantor Media, 2018)
The one and only resource on using adaptogenic mushrooms to boost immunity and promote whole body health the natural way. Adaptogenic mushrooms are one of today's buzziest superfoods, known for their ability to restore skin's youthful glow, increase energy levels, reduce brain fog, keep your hormone levels in check, and so much more. In Healing Mushrooms , you'll learn about the ten most powerful mushrooms you can add to your daily diet to maximize your health gains. Though some of these mushrooms, like Tremella, Cordyceps, and Reishi will sound exotic, they're all easy to source online in extract form and easier to use in recipes. Even more familiar mushrooms, like Shiitake, Oyster, and Enoki, are full of seriously healing potential—you just have to know how to use them. Packed with practical information and fifty mushroom-boosted recipes for breakfast, lunch, and dinner (and even dessert!), Healing Mushrooms unlocks the vast potential of this often-overlooked superfood category and will be the go-to resource for adding mushrooms to your health and wellness regimen.